Essential oils mix effect on chicks ileal and caecal microbiota modulation: a metagenomics sequencing approach - Girard, Claire; Chabrillat, Thibaut; Kerros, Sylvain; Fravalo, Philippe; Thibodeau, Alexandre (Frontiers in Veterinary Science, 2024)
Microbiota is a key in poultry health and well-being. Essential oils (EO's) are one of alternatives solutions used to modulate birds' microbiota. The aim of this study was to investigate, using amplicon sequencing, the effect of a complex and well-defined combination of EOs feed supplement on both ileal and caecal broiler microbiota in the context of Salmonella and Campylobacter intestinal colonization. A total of 150-day-old Ross chicks were randomly allocated to 2 groups: T+ (feed supplementation with EO mix 500g/t) and T-(non-supplemented). At D7, 30 birds from each group were orally inoculated with 10 6 CFU/bird of a Salmonella Enteritidis and moved to a second room, creating the following groups: TS+ (30 challenged birds receiving infeed EO mix at 500g/t) and TS-(30 challenged birds receiving a non-supplemented control feed). At D14, remaining birds in the first room were orally inoculated with 10 3 CFU/bird of 2 Campylobacter jejuni strains, creating groups T+C+ as well as T-C+. Animals were sacrificed at day 7, D10, D14, D17 and D21. Ileal and caecal microbiota samples were analysed by Illumina MiSeq sequencing. At D7 and D14 ileal alpha diversity were higher for treated animals (p<0.05). No difference between groups were found for caecal alpha diversity (p>0.05). Ileal beta diversity was different between groups at D7 (p<0.008), D10 (p=0.029), D14 (p=0.001) and D17 (p=0.018) but not at D21 (p=0.54). For all time points, analysis indicated 6 biomarkers negatively impacted and 10 biomarkers positively impacted. Sellimonas and Weissella returned the lowest (negative) and highest (positive) coefficient. At each time points, treatments impacted caecal microbiota beta diversity (p<0.001); 31 genera were associated to T+: 10 Ruminoccocaceae genera were alternatively more abundant and less abundant from D7, 7 Lachnospiraceae genera were alternatively more and less abundant from D10, 6 Oscillospiraceae genera were variable depending on the date and 4 Enterobacteriaceae differed from D7. During all the experiment, Campylobacter decreased in treated birds (p<0.05). This study showed that EO mix modulates ileal and caecal microbiota composition before and in challenged conditions, increasing alpha diversity, especially in ileum at the early stages of chick life.